Zinc Donor–Acceptor Schiff Base Complexes as Thermally Activated Delayed Fluorescence Emitters - Andreas Russegger; Lisa Eiber; Andreas Steinegger; Sergey M. Borisov (Chemosensors, 2022)
Four new zinc(II) Schiff base complexes with carbazole electron donor units and either a 2,3-pyrazinedicarbonitrile or a phthalonitrile acceptor unit were synthesized. The donor units are equipped with two bulky 2-ethylhexyl alkyl chains to increase the solubility of the complexes in organic solvents. Furthermore, the effect of an additional phenyl linker between donor and acceptor unit on the photophysical properties was investigated. Apart from prompt fluorescence, the Schiff base complexes show thermally activated delayed fluorescence (TADF) with quantum yields up to 47%. The dyes bearing a phthalonitrile acceptor emit in the green–yellow part of the electromagnetic spectrum and those with the stronger 2,3-pyrazinedicarbonitrile acceptor—in the orange–red part of the spectrum. The emission quantum yields decrease upon substitution of phthalonitrile with 2,3-pyrazinedicarbonitrile and upon introduction of the phenyl spacer. The TADF decay times vary between 130 µs and 3.5 ms at ambient temperature. The weaker phthalonitrile acceptor and the additional phenyl linker favor longer TADF decay times. All the complexes show highly temperature-dependent TADF decay time (temperature coefficients above −3%/K at ambient conditions) which makes them potentially suitable for application as molecular thermometers. Immobilized into cell-penetrating RL-100 nanoparticles, the best representative shows temperature coefficients of −5.4%/K at 25 °C that makes the material interesting for further application in intracellular imaging.